2007
DOI: 10.1021/jp068566i
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Octyl Cyanide at the Free Water Surface as Studied by Monte Carlo Simulation

Abstract: Monte Carlo simulations of the adsorption layer of octyl cyanide have been performed on the canonical (N, V, T) ensemble at 300 K. The systems simulated cover the range of octyl cyanide surface densities from 0.27 to 7.83 mumol/m2. The surface density value at which the saturation of the adsorption layer occurs is estimated to be 1.7 mumol/m2. At low surface densities, the main driving force of the adsorption is found to be the formation of hydrogen bonds between the water and octyl cyanide molecules, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…This point is further investigated in a following subsection of the paper. It should be noted that similar behavior of the mass density profile upon saturation of the adsorption layer was observed previously for various nonionic surfactants. ,, …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This point is further investigated in a following subsection of the paper. It should be noted that similar behavior of the mass density profile upon saturation of the adsorption layer was observed previously for various nonionic surfactants. ,, …”
Section: Resultssupporting
confidence: 83%
“…Thus, in these systems about 20% and 50% of the DS − ions have a tilt angle smaller than 15° and 30°, respectively, relative to the macroscopic surface normal axis. This change in the orientation of the DS − ions with their increasing surface density is rather similar to what was previously observed in the adsorption layer of various nonionic surfactants, ,, and can be explained by the decreasing surface area available for the individual molecules, namely by the fact that maximizing the number of DS − ions attached to the surface requires minimizing the surface area occupied by the individual surfactant ions, which can be done by adopting the orientation perpendicular to the aqueous surface.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It was reported that the main driving force of the adsorption is the possibility of forming hydrogen bonds between the adsorbed octyl cyanide and interfacial water molecules. [32] Therefore, the calculated populations to characterize the hydrogen bonds formed by water and 6CB molecules are given in Table 4. We define 6CB and water molecules to be hydrogen bonded if their nitrogen-oxygen distances are less than 3.35 Å and simultaneously the nitrogen-hydrogen distance is less than 2.45 Å.…”
Section: 𝜃Core (Deg)mentioning
confidence: 99%
“…But, one of the difficulties for such simulations is the adequate definition of effective interactions between the Bgrains.Î nvestigations of the surfactant behavior at different interfaces using the Monte Carlo method are not so numerous. Nevertheless, corresponding studies enable the estimation of the structural features for surfactant films [132,133], chiral effects in monolayers [134], impact of the structural peculiarities of the surfactants on the parameters of the phase transitions in the monolayers [135]. In the framework of the continuum configurational bias Monte Carlo method Howes and Radke [132] got surface tension isotherms of nonionic amphiphiles and calculated the tilt angles of the surfactant molecules with respect to the interface.…”
Section: Molecular Mechanicsmentioning
confidence: 99%